Peranan Pseudomonas aeruginosa ATCC 15442 terhadap Pertumbuhan Tanaman Cabai Rawit (Capsicum frutescens L.) Varietas Bonita pada Kondisi Salin: The Role of Pseudomonas aeruginosa ATCC 15442 on the Growth of Bonita Hot Pepper (Capsicum frutescens L.) Variety in Saline Conditions - Aas Ratnasari; Nisa Rachmania Mubarik; Aris Tjahjoleksono (Jurnal Sumberdaya Hayati, 2023)
Hot pepper (Capsicum frutescens L.) is one of the food crop commodities that is widely cultivated in Indonesia. Salinity stress can reduce the bioavailability of potassium and its uptake by plants, which will ultimately reduce plant growth and production. One way to reduce the effect of salinity and increase potassium uptake by plants is to use potassium-solubilizing bacteria. One of the bacteria that can solubilize potassium is Pseudomonas aeruginosa. This research aims to study the role of Pseudomonas aeruginosa ATCC 15442 on the growth of the Bonita variety of hot pepper under saline conditions. This study used a completely randomized factorial design with four concentration levels of NaCl treatment: 0, 4, 8, and 12 g/L, as well as two levels of bacteria administration: without bacteria and with bacteria. The results showed that the application of bacteria, salt concentration, and the interaction of the two had no effect (p-value> 0.05) on the growth of hot pepper plants with the observed parameters namely plant height, number of leaves, shoot fresh weight, root fresh weight, shoot dry weight, root dry weight, and chlorophyll content.